La vida que se enfrenta a la muerte: el espíritu y su experiencia de la negatividad en el prólogo a la Fenomenología del Espíritu - Prendas Solano, Jorge (2008)
This article intends to make a lecture of Hegel’s prologue of the Phenomenology of the Spirit, concentrating on the category of negativity and at the same time marking some important elements which could be drawn from the study of this subject to any general thought and philosophy in Latin America.